Development Modified Conjugate Gradiente Algorithm - Abbas H. Taqi; Amal N. Shaker (Tikrit Journal of Pure Science, 2023)
In this paper was to develop method V1-CG methods associated gradient amended to increase the speed of the convergence while retaining the charactenstic mass convergence as the derivation of this method was based on strict convex quadratic function has been develop this way to public function in whichthe supreme derivatives not equal zero.